Uma compreensão psicossomática do órgão de choque através do trabalho com polaridades - Ivancko, Silvia Martins (2006)
The objective of this work was to investigate the relationship of the psychic functioning in chock organ, in twenty subjects considered healthy. The subjects were indicated by acquaintance, and were volunteers what were attended individually. As a procedure, was used the active imagination, directed by the researcher, focusing the main organs and systems of the organism. To conclude this phase, the subjects had to elect a fragile and a strong organ of their body. The next phase from the election of these organs, the subjects experienced the empty chair procedure, where they supposedly sit their chock organ on a chair in front of them to talk to this organ, switching chair and roles. This procedure helped the subjects to know about their polarities and content projected in the organs. After this, the same procedure was repeated, but at this time with the organ chosen as strong. From these dialogues was possible to identify the psychic content of the subject, in the parts represented by those organs. The identification of the psychic contents occurred through a phenomenological analysis of the contents projected to the elected organs and happened in partnership with the subject. Followed five support sessions were we worked with the subjects, individually, the psychic functioning projected in the chock organ. Two months after the last support session, there was an evaluation of the results where was found a perceptible improvement of the contact with the chock organ. The subjects established relationship of the psychic functioning with the impacts in their chock organ, where the greater part presented improvement of the symptoms and in some cases absent of them